2015
DOI: 10.1089/cap.2014.0097
|View full text |Cite
|
Sign up to set email alerts
|

Participant Satisfaction in a Study of Stimulant, Parent Training, and Risperidone in Children with Severe Physical Aggression

Abstract: Treatment of Severe Childhood Aggression (The TOSCA Study), NCT00796302, clinicaltrials.gov .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Similar to prior studies of parent study satisfaction [ 2 , 5 7 , 21 ], most TEDDY parents were very satisfied with their study participation; over 45% of mothers and over 38% of fathers had the highest possible satisfaction score after 1 year and 4 years in the study. DPT-1 [ 12 , 13 ] used the same questions to measure satisfaction as in this study and their results were similar to ours with high parental satisfaction among both mothers and fathers.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar to prior studies of parent study satisfaction [ 2 , 5 7 , 21 ], most TEDDY parents were very satisfied with their study participation; over 45% of mothers and over 38% of fathers had the highest possible satisfaction score after 1 year and 4 years in the study. DPT-1 [ 12 , 13 ] used the same questions to measure satisfaction as in this study and their results were similar to ours with high parental satisfaction among both mothers and fathers.…”
Section: Discussionsupporting
confidence: 77%
“…This dearth of literature is particularly noteworthy in pediatric populations. Published studies of parent satisfaction focus mostly on the child’s care or specific aspects of a study [ 2 6 ], but studies of parents’ overall satisfaction with a study in which their child is enrolled are limited. The studies that do exist suggest that most participating parents will recommend the study to others and are willing to participate in a new study [ 2 , 5 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis identified brief interventions including motivational interviewing and discussions of barriers to seeking care (e.g., transportation, resistance to treatment) as being effective in enhancing early engagement in treatment (Ingoldsby 2010). Importantly, parent participants of the TOSCA study reported high levels of satisfaction with the PT component of the trial with 71% rating PT as very helpful (Rundberg-Rivera et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Equally important was the failure of our proactive and reactive aggression measure to moderate outcomes. Finally, Rundberg-Rivera et al (2015) surveyed 150 of the participating families and reported remarkably high levels of satisfaction with the research experience (e.g., 98% said that they would recommend the study to other parents of children having similar difficulties). Parents enthusiastically endorsed the PT provided, and it seemed to be an important part of the TOSCA experience.…”
Section: Treatment Of Severe Childhood Aggression (Tosca) Studiesmentioning
confidence: 99%